2018
DOI: 10.1038/s41598-018-32822-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the antimicrobial mechanism of porcine beta defensin 2 against E. coli by electron microscopy and differentially expressed genes

Abstract: Porcine beta defensin 2 (pBD2) is a cationic antimicrobial peptide with broad spectrum antibacterial activity, which makes it a potential alternative to antibiotics to prevent and cure diseases of pigs. However, development of pBD2 as an effective antibiotic agent requires molecular understanding of its functional mechanism against pathogens. In this study, we investigated the functional mechanism of pBD2 antibacterial activity. Escherichia coli was incubated with different pBD2 concentrations for different ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Similarly, MIC of rPBD114 protein was carried out and rPBD114 protein exhibited antimicrobial activity against E. coli but not Gram-positive bacteria and fungus. However, a great number of studies have shown that defensins have a wide range of antimicrobial activities [34–37]. The antimicrobial activity of rPBD114 protein in our study suggested that Pichia pastoris X 33 would be more tolerant to expression of rPBD114.…”
Section: Discussionmentioning
confidence: 50%
“…Similarly, MIC of rPBD114 protein was carried out and rPBD114 protein exhibited antimicrobial activity against E. coli but not Gram-positive bacteria and fungus. However, a great number of studies have shown that defensins have a wide range of antimicrobial activities [34–37]. The antimicrobial activity of rPBD114 protein in our study suggested that Pichia pastoris X 33 would be more tolerant to expression of rPBD114.…”
Section: Discussionmentioning
confidence: 50%
“…Such changes were attributed by others to bacteria damage and death caused by the contact with antimicrobial materials. [29][30][31] In turn, S. aureus was less sensitive to N,N-dimethyl-N-n-octylammonium groups. In few places, damaged and dead bacteria were seen on FrGO I fibers but they were overgrown by other microorganisms without noticeable damage, as evidenced in Figure 5(G).…”
Section: Resultsmentioning
confidence: 99%
“…The ability of avian defensins to chemoattract immune cells also contribute to their antibacterial activities [ 51 ]. Although the antibacterial mechanism of PBD-2 against Staphylococcus aureus and E. coli has been characterized as being membrane disruption and regulation of DNA transcription and translation after PBD-2 is present in the cytoplasm [ 55 , 56 ], the antibacterial mechanism of PBD-2 against G. parasuis is unclear and requires further studies.…”
Section: Discussionmentioning
confidence: 99%